2018
DOI: 10.1523/jneurosci.1421-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal–Bed Nucleus Circuit Modulation of a Passive Coping Response Set

Abstract: One of the challenges facing neuroscience entails localization of circuits and mechanisms accounting for how multiple features of stressresponses are organized to promote survival during adverse experiences. The rodent medial prefrontal cortex (mPFC) is generally regarded as a key site for cognitive and affective information processing, and the anteroventral bed nuclei of the stria terminalis (avBST) integrates homeostatic information from a variety of sources, including the mPFC. Thus, we proposed that the mP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 101 publications
5
35
0
Order By: Relevance
“…Involvement of the PrL is consistent with its prominent role in mediation of coping behavior (Fiore et al, 2015;Johnson et al, 2019;Molendijk and de Kloet, 2019).…”
Section: Physiological Impact Of Chronic Stresssupporting
confidence: 59%
See 1 more Smart Citation
“…Involvement of the PrL is consistent with its prominent role in mediation of coping behavior (Fiore et al, 2015;Johnson et al, 2019;Molendijk and de Kloet, 2019).…”
Section: Physiological Impact Of Chronic Stresssupporting
confidence: 59%
“…Involvement of the PrL is consistent with its prominent role in mediation of coping behavior (Fiore et al, 2015;Johnson et al, 2019;Molendijk and de Kloet, 2019). As part of our design, we assessed the impact of IL PV IN inhibition acutely following the first stressor in our CVS regimen, the TST, which allows for a behavioral readout (duration of struggling, immobility and latency to immobility).…”
Section: Chronic Inhibition Of Pv Ins During Cvs: Impact On Physiologmentioning
confidence: 99%
“…In human beings, the symptoms of passive coping response are referred to as hopelessness, which is a core feature of major depressive disorder. It has been shown that mPFC also plays a role in the control of the passive coping response to behavioral challenge 20‐22,29 . By using pharmacological and shRNA interventions, our previous study demonstrates an involvement of P2X2 receptors in the mPFC in the ATP modulation of passive coping response 12 .…”
Section: Discussionmentioning
confidence: 86%
“…The FST and TST are widely employed to evaluate the despair aspect of depression‐like behavior and screen antidepressants in rodents, 18 but recently researchers prefer to interpret the acquisition of immobility in the FST as behavioral adaptation to the acute stressor which represents an adaptive cognitive process or as passive coping response or inhibition of active coping response 19‐22 . In this study, we used the FST and TST to measure passive coping response to behavioral challenge.…”
Section: Resultsmentioning
confidence: 99%
“…In another group of CRH neurons, the BNST input attenuates the sympathetic output. A separate pathway of the BNST projects to the ventrolateral periaqueductal (vl-PAG) where passive coping is promoted at the expense of the initial active coping strategy [89,90]. Active coping refers to fight or flight, which, when the situation is appraised as inescapable, causes a reorganization of prelimbic to infralimbic mPFC circuitry that is aimed to restrain the emotional and autonomic responses [91][92][93][94].…”
Section: Functional Cooperation Of Mr and Grmentioning
confidence: 99%